The Influence of Work Discipline and Teamwork on Employee Performance with Organizational Citizenship Behavior as An Intervening Variable In The Employment BPJS Branch Se-Medan Raya - Deliana, Lasmaida Susy; Ferine, Kiki Farida (Neo Journal of economy and social humanities, 2024)
In this study, the researcher wants to see the direct and indirect influence between the variables of Work Discipline, Teamwork as independent variables with Organizational Citizenship Behavior as intervening variables and Employee Performance as dependent variables. This type of research uses quantitative, this research was conducted at BPJS Ketenagakerjaan Kanwil North Sumatra. The population of this study was 82 employees and the sample used was the entire population using saturated sampling techniques. The data source used is the primary data source and data collection was carried out by distributing questionnaires. The research model used is phat analysis with smart PLS version 3.3.3. as a research measuring tool. The results of this study are as follows Work Discipline has a positive and insignificant effect on employee performance with an original sample value of 0.585 and P values ​​0.218. Work Discipline has a negative and significant effect on Organizational Citizenship with an original sample value of -0.949 and p values ​​0.000. Teamwork has a negative and insignificant effect on Employee Performance with an original sample value of -0.694 and p values ​​0.304. Teamwork has a positive and significant effect on Organizational Citizenship with an original sample value of 1.720 and p values ​​of 0.000. Organizational Citizenship has a positive and significant effect on Employee Performance with an original sample value of 1.024 and p values ​​of 0.003. Work Discipline has a negative and significant effect on employee performance through organizational citizenship indirectly with an original sample result of -0.981 and p values ​​of 0.011. Teamwork has a positive and significant effect on employee performance through organizational citizenship indirectly with an original sample result of 1.775 and p values ​​of 0.001.